FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS INTERNATIONAL CRIMINAL COURT DALAM PENYELESAIAN KONFLIK UGANDA The Factors Affecting Effectiveness of International Criminal Court’s Role in Finishing Uga - Nisrina Ainun Nisa (HI 16 UMY 113, 2016)
*113 This research aims to explain the effectiveness of ICC (International Criminal Court) in handling conflict in Uganda. The research used qualitative design to gather description of ICC handling incident that has been harm to society. Technique of data collection method is secondary data. Secondary data use literature material such as books, journals, and articles. Researcher also support data by downloading data on several site from internet which relevant with aim of the research. This research discuss analytical description about effectiveness of ICC (International Criminal Court) toward the rebellion of Lord’s Resistance Army (LRA) in Uganda. ICC (International Criminal Court) is international independent organization that strive for genocide, crimes against humanity, war crimes and crime of aggression. LRA is group of insurgent that has been operate in Uganda. LRA become a threat in Africa countries caused by their conflict against Uganda government. LRA use violence strategy to get their authority. Leader and stakeholder of LRA get arrest warrant from ICC for justice by considering the evidence that has been get by ICC.